Peningkatan Pemahaman terhadap Isu Gender di Masyarakat melalui Project Photovoice oleh Siswa SMA Negeri di Purwokerto, Jawa Tengah - Trisnawati, Ririn Kurnia; Agustina, Mia Fitria; Adiarti, Dian; Sari, Eka Dyah Puspita (Warta LPM, 2025)
Gender issues are not unfamiliar around Indonesian people. However, it does not mean that everyone in Indonesia understands the issues. For this problem, an understanding about gender issues is needed and the target of this community service program is students of SMAN 5 Purwokerto.  The SMAN 5 Purwokerto students are the target for this activity as the method that is used for this community service is photovoice, a literacy method that uses photo and caption which are suitable for their age. This community service aims at raising understanding and awareness about gender issues to the young generation to prevent gender discrepancy. By giving materials about gender issues, writing captions, photography training, and mentoring, the result of this program is the SMAN 5 Purwokerto students' understanding  regarding gender issues. This result is proven by their answers on pretest and post-test which were given before and after the program. The pretest results showed that there were some students who did not understand the terms and descriptions related to gender issues (20%), while the post-test results showed that all students could provide and explain photovoice with gender issues (100%). This shows that the photovoice activity was successful in improving students' understanding of gender issues.